2016
DOI: 10.1159/000453579
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection in the Elderly: Possible Relationship with Guillain-Barré Syndrome

Abstract: The Zika virus (ZIKV) outbreak in French Polynesia, in 2013, and in Brazil, in 2015, was correlated with neurological complications, which comprised, among others, congenital microcephaly and Guillain-Barré syndrome (GBS), which includes a group of acute autoimmune neuropathies generally reported after respiratory or gastrointestinal infectious diseases. Despite being relatively rare, the incidence rate of GBS rises with age, which makes GBS more frequent in the elderly, in whom it is also a more severe diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A study performed in Slovenia revealed that after elective termination of pregnancy, ZIKV viral particles were detected in brain tissues of the fetus diagnosed with microcephaly [5] and ZIKV RNA was also identified in the amniotic fluid of pregnant women who delivered microcephalic babies [4]. Besides microcephaly, other neurological abnormalities were detected in babies born to infected mothers including cerebral calcifications, cerebellar dysplasia, ocular lesions, hearing loss and arthrogryposis [6]. Because ZIKV infection correlated with several neurological abnormalities during fetal development, the concept of congenital ZIKV syndrome has been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed in Slovenia revealed that after elective termination of pregnancy, ZIKV viral particles were detected in brain tissues of the fetus diagnosed with microcephaly [5] and ZIKV RNA was also identified in the amniotic fluid of pregnant women who delivered microcephalic babies [4]. Besides microcephaly, other neurological abnormalities were detected in babies born to infected mothers including cerebral calcifications, cerebellar dysplasia, ocular lesions, hearing loss and arthrogryposis [6]. Because ZIKV infection correlated with several neurological abnormalities during fetal development, the concept of congenital ZIKV syndrome has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, ZIKV infection is associated to Guillain-Barré syndrome [6, 7]. By March 2017, 31 countries and territories have reported cases of microcephaly and other central nervous system abnormalities possibly related to ZIKV infection during pregnancy, and 23 countries and territories have reported increased incidence of Guillain-Barré syndrome [8].…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV infection may trigger GBS (severe neuropathies) (Savino et al, 2017; Zhou et al, 2017; Hygino da Cruz et al, 2018; Wu et al, 2018) and it is closely associated with congenital Zika diseases (microcephaly and brain abnormalities) in humans (Franca et al, 2016; Shapiro-Mendoza et al, 2017; Zorrilla et al, 2017). ZIKV RNA replication has been identified in human brain and placental tissues (Bhatnagar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the risks related to the infection, including congenital malformations, prophylaxis against ZIKV infection is still an urgency, and the best answer is vaccinating people in risk areas, mostly susceptible populations. Pregnant women 7 , elderly 20 and immunocompromised individuals 21 deserve special attention. Several vaccine types against ZIKV are currently in phase I clinical trials, including DNA vaccines, mRNA-based, inactivated virus, peptide, and recombinant viral vectored vaccines 22 .…”
Section: Introductionmentioning
confidence: 99%